Geographic and Temporal Variation in Annual Survival of a Declining Neotropical Migrant Hummingbird (Selasphorus rufus) Under Varying Fire, Snowpack, and Climatic Conditions - Drake, Anna; Bishop, Christine A.; Moran, Alison J.; Wilson, Scott (Frontiers in Ecology and Evolution, 2022)
Rufous hummingbirds (Selasphorus rufus) have shown consistent declines in abundance since 1970, with an acceleration in this trend starting in the mid-2000s. Demographic data is needed to isolate possible drivers. We employ mark-recapture data to calculate sex-specific adult apparent annual survival, accounting for residency probability, within the coastal and interior regions of British Columbia, Canada between 1998-2017. For the coastal region, we also examine associations between apparent survival and a suite of migratory factors: the amount of recently- and historically-burned flyway habitat, fall moisture availability in the alpine (snowpack), and a broad-scale climate index (SOI), under the assumption that these factors are associated with food availability during a critical period of the annual cycle. We find no trend in adult apparent survival over the 20-year period, implicating changes in recruitment rather than adult survival as driving the declining trend in abundance. Interior birds of both sexes showed lower residency probability than coastal individuals suggesting interior sites captured more late northbound individuals or more early southbound individuals within the breeding period. Adult apparent annual survival was not correlated with any of the migratory variables we examined. Our findings suggest a need to focus on juvenile recruitment as a possible driver of the long-term declines in Rufous Hummingbirds. Future studies should consider both potential threats to productivity on the breeding grounds and to juvenile survival on the nonbreeding grounds.